Keterlibatan Perempuan dalam Pengelolaan Aktivitas Wisata Studi Kasus Desa Ekowisata Pancoh, Yogyakarta - Mulyasari, Runavia; Maizida, Karlina (Journal of Indonesian Tourism, Hospitality and Recreation, 2024)
ABSTRACTThis study explores women's participation in managing community-based tourism in Pancoh Ecotourism Village. Strengthening women’s roles as innovators, leaders, and decision-makers is crucial for tourism recovery post-pandemic. Using a qualitative approach, data were collected through semi-structured interviews and focus group discussions (FGD) with 35 participants, including tourism actors, business managers, youth communities, women activists, and academics. Over 12 months, interviews, FGDs, and seminars were conducted to assess the level of female involvement in tourism management. The findings reveal that although women actively participate in tourism activities, only a few hold leadership positions or serve as decision-makers.Women's participation is categorized into two main groups:older women who manage accommodations (homestays) and younger women involved in guiding tours. Socio-cultural values, particularly the perception that women are primarily responsible for domestic duties, limit their involvement in higher-level management. This research highlights the need for more inclusive tourism planning that involves women and youth in leadership roles, contributing to a more equitable development of tourism.ABSTRAKPenelitian ini mengeksplorasi partisipasi perempuan dalam pengelolaan pariwisata di Desa Ekowisata Pancoh. Penguatan peran perempuan sebagai inovator, pemimpin, dan pengambil keputusan menjadi penting dalam pemulihan pariwisata pasca pandemi. Dengan pendekatan kualitatif, data dikumpulkan melalui wawancara semi-terstruktur dan diskusi kelompok terarah yang melibatkan 35 peserta, termasuk pelaku pariwisata, pengelola bisnis, kelompok pemuda, aktivis, dan akademisi. Hasil penelitian yang dilakukan selama 12 bulan menunjukkan bahwa meskipun perempuan aktif dalam kegiatan pariwisata, hanya sedikit yang menduduki posisi kepemimpinan atau pengambil keputusan. Partisipasi perempuan dibagi menjadi dua kelompok utama: pengelola homestay dan pemandu wisata. Nilai-nilai sosial-budaya, terutama anggapan bahwa perempuan memiliki tanggung jawab utama di ranah domestik, membatasi keterlibatan mereka dalam manajemen tingkat atas sehingga, diperlukan adanya perencanana pariwisata yang lebih inklusif.